Virtual tutoring in the academic and human formation of UNAMBA students - Cari-Incahuanaco, Francisco (2023)
Time has been a primordial witness in the evolution of human knowledge; day by day, as a result of human ingenuity, an impressive amount of technological novelties appear, breaking all kinds of barriers and increasing the interest in designing new virtual tools that lead to multidisciplinary learning [1]. This research determines the contribution of virtual tutoring in the academic and human formation of students of the Universidad Nacional Micaela Bastidas de Apurímac; virtual tutoring is a process of accompaniment during the training of tutored students, through personalized attention to students by tutor teachers, conceptually supported by learning theories that enable a better approach to students, whose work of the tutor teacher is to help students learn to successfully complete their professional career, it is also very important to mention the existence of a mutual relationship between tutor and tutored, in this interrelationship virtual communication should be fluid and harmonious between the two actors. The results obtained in the specific hypothesis tests show that virtual tutoring contributes significantly to the academic formation of UNAMBA students; thus, the surveys show that virtual tutoring contributes to the human formation of UNAM-BA students.